Peran Penerapan Good Dairy Farming Practices (GDFP) dan Kesejahteraan Peternak terhadap Kinerja Usaha Sapi Perah - Susanti, Febri Velindria; Relawati, Rahayu; Ishartati, Erny (Lembaga Teewan Journal Solutions, 2026)
The sustainability of smallholder dairy farming relies heavily on the adoption of technical standards for milk handling and the well-being of farmers, who act as the primary decision-makers in the field. This study aims to analyze the impact of implementing Good Dairy Farming Practices (GDFP) and farmer well-being (economic, psychological, and social) on the financial performance of smallholder dairy businesses. A quantitative research method was employed, utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4 software The analysis results indicate that the model has very strong predictive capability regarding business profit (R² = 90.8%). Based on path coefficients, milk quality emerged as the variable with the most dominant and substantial effect on business profit (p = 0.000), followed by productivity (p = 0.000). Analysis of indirect effects demonstrates that productivity and milk quality serve as full mediators, bridging on-farm GDFP technical practices with financial profit. Meanwhile, farmers' psychological well-being acts as the primary driver of business management discipline (p = 0.000). All hypothesized moderating effects of economic well-being were rejected (p > 0.05), indicating that farmers' operational management capabilities operate independently of their personal financial stability. Dairy cooperatives are advised to tighten milk quality testing systems at collection points. Furthermore, they should provide high-quality teat dip solutions, stainless steel milking buckets, and sterile milk cans to minimize bacterial contamination. The government should prioritize management literacy training programs, interactive technical guidance, and group mentoring initiatives designed to boost farmers' motivation and mental welfare (psychological welfare).